Antioxidant Activity of Mushroom Extracts/Polysaccharides-Their Antiviral Properties and Plausible AntiCOVID-19 Properties - Sechul Chun; Judy Gopal; Manikandan Muthu (MDPI AG, 2021)
Mushrooms have been long accomplished for their medicinal properties and bioactivity. The ancients benefitted from it, even before they knew that there was more to mushrooms than just the culinary aspect. This review addresses the benefits of mushrooms and specifically dwells on the positive attributes of mushroom polysaccharides. Compared to mushroom research, mushroom polysaccharide-based reports were observed to be significantly less frequent. This review highlights the antioxidant properties and mechanisms as well as consolidates the various antioxidant applications of mushroom polysaccharides. The biological activities of mushroom polysaccharides are also briefly discussed. The antiviral properties of mushrooms and their polysaccharides have been reviewed and presented. The lacunae in implementation of the antiviral benefits into antiCOVID-19 pursuits has been highlighted. The need for expansion and extrapolation of the knowns of mushrooms to extend into the unknown is emphasized.